Randomised comparison of achieve and traditional circular mapping catheters in cryoballoon ablation: results at up to a decade. (19th May 2022) - Gallagher, M; Akhtar, Z; Gang, Y; Gonna, H; Li, A; Bajpai, A; Zuberi, Z; Norman, M; Sohal, M; Leung, LWM
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: A single-centre trial randomised patients to the use of the Achieve mapping catheter or a traditional circular mapping catheter during cryoballoon procedures for paroxysmal atrial fibrillation (AF) in 2011-2014. Long-term outcomes from the cohort were determined in 2021. Purpose: To evaluate the determinants of long-term outcome of ablation for paroxysmal AF. Methods: Patient and study procedure characteristics and clinical outcomes were determined, including mapping catheter assignment, model of cryoballoon used, AF recurrence, repeat ablations required, findings at repeat ablation long term survival of the patient. Results: Of 102 patients in the original study, 98 had long-term (4.11+/-2.82 years) follow up data available. 35 patients (35.7%) had AF recurrence, giving a long-term success rate at 64.3% after 1 ablation, increasing to 81.6% after repeat ablation. Of the study cohort n=8 (8.16%) died at a median of 4.9 years after ablation (IQR:1.7-5.7). 25/98 (25.5%) patients had a second ablation and 7 (7.1%) had a third or more ablations. Those who had AF recurrence were older, with a higher prevalence of prior ischaemic heart disease and cardiac device implantation (p=0.02-0.03). After multi-variate analysis, a prior implanted cardiac device was the only significant predictor of recurrence (p=0.03). Conclusion: Long-term outcomes after a 1st time PAF cryoablation were similar regardless of the type of mapping catheter used, the generation of cryoballoon, and traditional procedure endpoints. AF recurrences were more often detected in older patients with a history of ischaemic heart disease and implanted cardiac devices.